Single LED-Based Indoor Positioning System Using Multiple Photodetectors - Xiaohui Yu; Jianping Wang; Huimin Lu (IEEE Photonics Journal, 2018)
This paper presents a visible light positioning system using a single light-emitting diode (LED) and a novel receiver. In the proposed system, the receiver is composed of a horizontal photodetector (PD) and two tilted PDs, and a known calibration point is deployed to improve the accuracy of the positioning. Based upon the multi-PDs’ relative positions and the received signal strength, the location of the receiver can be estimated regardless of the LED's and PDs’ characteristics. The influences of tilted PDs on the positioning errors are discussed, i.e., the polar angle α and the difference θ between two azimuth angles. The experimental results show that high accuracy can be achieved when α = 20° and θ ranges from 30° to 90°. The average and maximum errors are 2.15 and 4.01 cm, respectively, in the case of α = 20° and θ = 45°. The proposed system avoids the intercell interference caused by different transmitters and can be applied in scenarios with limited LEDs.